Listeria monocytogenes: A CONSIDERABLE PATHOGENIC MICROORGANISM OF CONCERN IN MINIMALLY PROCESSED FRUITS AND VEGETABLES - Helen C D Tuhumury (AGRITEKNO: Jurnal Teknologi Pertanian, 2017)
The increasing demand of minimally processed fruits and vegetables signify a challenge to make them stable and safe to be consumed. The processing of this type of product may contribute higher risks of food borne illnesses. One of the foodborne pathogens in minimally processed fruits and vegetables is Listeria monocytogenes. The importance of understanding the characteristics of L. monocytogenes will help to determine how this microorganism occurs, grows, and survives in minimally processed fruits and vegetables. Proper and suitable methods to reduce L. monocytogenes so that it can not pose a significant risk to cause disease therefore are able to be determined according to the model of the growth and survival of L. monocytogenes in minimally processed fruits and vegetables.